2021
DOI: 10.3892/mmr.2021.12440
|View full text |Cite
|
Sign up to set email alerts
|

PLAC1 is an independent predictor of poor survival, and promotes cell proliferation and invasion in cervical cancer

Abstract: Placenta-specific protein 1 (PLAC1) is inversely associated with survival in several types of cancer. However, whether PLAC1 is involved in the progression of cervical cancer (CC) remains to be elucidated. Therefore, the present study aimed to evaluate the prognostic role of PLAC1 in CC by determining the relationship between clinicopathological factors, PLAC1 gene expression and survival prognosis using univariate and multivariate Cox proportional-hazards regression analyses. Similarly, Kaplan-Meier curves we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The prognostic value of vimentin expression determined in tumor cells by immunohistochemistry before treatment was previously shown using univariate and multivariate analyses of overall and disease-free survival of patients with squamous cell CC and adenocarcinoma of the uterine cervix [ 40 , 41 , 42 , 43 ]. In addition, there have been growing data on the association of other EMT markers, including the transcription factors Snail, Slug, Twist, ZEB1, etc., and EMT-related molecules with poor prognosis of long-term clinical outcome [ 43 , 44 , 45 , 46 ]; at the same time, inhibitors or negative modulators of EMT were found to be factors of favorable prognosis of CC patients [ 47 , 48 ]. Taking into account these data, it made sense to analyze the informativeness of the vimentin expression assessment in non-invasive material of scrapings from the cervix before treatment to predict the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of vimentin expression determined in tumor cells by immunohistochemistry before treatment was previously shown using univariate and multivariate analyses of overall and disease-free survival of patients with squamous cell CC and adenocarcinoma of the uterine cervix [ 40 , 41 , 42 , 43 ]. In addition, there have been growing data on the association of other EMT markers, including the transcription factors Snail, Slug, Twist, ZEB1, etc., and EMT-related molecules with poor prognosis of long-term clinical outcome [ 43 , 44 , 45 , 46 ]; at the same time, inhibitors or negative modulators of EMT were found to be factors of favorable prognosis of CC patients [ 47 , 48 ]. Taking into account these data, it made sense to analyze the informativeness of the vimentin expression assessment in non-invasive material of scrapings from the cervix before treatment to predict the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The Transwell migration and invasion assays were performed as previously described. 9 The migrated or invaded cells were photographed under a light microscope, and the cell numbers were counted in five random fields per chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies confirmed its expression in more than 74 cancer cell lines (Silva et al, 2007;Mahmoudian et al, 2019). Including prostate (Ghods et al, 2014a;Nejadmoghaddam et al, 2017), breast (Koslowski et al, 2007;Li et al, 2018), uterus (Devor et al, 2014), cervix (Chen et al, 2021), ovary (Devor et al, 2017). In addition to, lung , liver (Wu et al, 2017), colon (Ren et al, 2020), gastric (Liu et al, 2021), pancreatic cancers (Yin et al, 2017), nasopharyngeal carcinomas (Lin et al, 2021), melanoma (Mahmoudi et al, 2020), and osteosarcoma (Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 95%